Urbanization Contributes Little to Global Warming but Substantially Intensifies Local and Regional Land Surface Warming. Issue 5 (13th May 2022) - Zhou, Decheng; Xiao, Jingfeng; Frolking, Steve; Zhang, Liangxia; Zhou, Guoyi
Abstract: Increasing urbanization causes an urban heat island (UHI) effect and exacerbates health risks of heat waves due to global warming. The surface UHI (SUHI) in large cities has been extensively studied, yet a systematic evaluation on the impacts of urbanization on local‐to global‐scale land surface warming is lacking. We propose a new procedure to quantify the warming effects of urbanization at local, regional, and global scales using high‐resolution satellite observations. We find strong local warming effects for 88% of the urban‐dominated pixels across the globe and cooling effects for the rest of the urban lands on a diurnal mean timescale, with a global urban mean intensity of 1.1°C in 2015. The SUHI effects differ substantially by time of day, season, and climate zone, and are closely related to surface evapotranspiration. By extending local effects to the entire land surface, we estimate a diurnal mean warming of only 0.008°C globally. However, urbanization can have large warming effects regionally, especially in eastern China, the eastern United States, and Europe. In addition, we show that global urban expansion results in over three‐quarters of SUHI effects in 1985–2015, and its effect will likely increase by 50%–200% by the end of this century. The SUHI‐added warming could be up to 0.12°C in summer in Europe by 2100 under a fossil‐fueled development pathway. Our results reveal that urbanization substantially intensifies local and regional land surface warming and that prioritized attention should be given to the SUHI‐added warming in highly or rapidly urbanized regions. Plain Language Summary: Rapid urban expansion can increase temperature by the resultant urban heat island effect, therefore exacerbating negative impacts of global warming on the environment, human health, and energy consumption. However, the magnitude by which global urbanization intensifies land surface warming is not well understood. We proposed a new procedure to quantify the effects of urban land use on local‐, regional‐, and global‐scale land surface warming using high‐resolution satellite observations. It is shown that urban expansion substantially warms local and regional climates, with high spatial‐temporal variability, but contributes little to global‐scale warming, and that the impacts are projected to nearly triple under a fossil‐fueled development pathway by the end of this century. This study offers a new perspective of methods to quantify the surface urban heat island effect and important insights for climate change assessments. Key Points: Impacts of urbanization on local‐to global‐scale land surface warming are quantified according to high‐resolution satellite observations Urbanization contributes little to global warming but greatly intensifies local and regional warming with large spatiotemporal variability Urban expansion leads to over 3/4 of the current urban heating effects in 1985–2015 and likely a 50%–200% further increase globally by 2100